Mutations of the aminoacyl‐tRNA‐synthetases SARS and WARS2 are implicated in the etiology of autosomal recessive intellectual disability. Issue 6 (23rd March 2017) - Musante, Luciana; Püttmann, Lucia; Kahrizi, Kimia; Garshasbi, Masoud; Hu, Hao; Stehr, Henning; Lipkowitz, Bettina; Otto, Sabine; Jensen, Lars R.; Tzschach, Andreas; Jamali, Payman; Wienker, Thomas; et al.
Abstract : We report mutations in two aminoacyl‐tRNA synthetases that are associated with intellectual disability. The first is a homozygous missense mutation (c.514G>A, p.Asp172Asn) in the cytoplasmic seryl‐tRNA synthetase ( SARS ) gene. It affects the enzymatic core domain of SARS and impairs its enzymatic activity. Secondly, we found a compound heterozygous genotype of the mitochondrial tryptophanyl‐tRNA synthetase ( WARS2 ) gene, comprising a nonsense mutation (c.325delA, p.Ser109Alafs*15), which very likely entails nonsense‐mediated mRNA decay, and a missense mutation (c.37T>G, p.Trp13Gly), which causes protein mislocalization. Abstract: Intellectual disability (ID) is the hallmark of an extremely heterogeneous group of disorders that comprises a wide variety of syndromic and non‐syndromic phenotypes. Here, we report on mutations in two aminoacyl‐tRNA synthetases that are associated with ID in two unrelated Iranian families. In the first family, we identified a homozygous missense mutation (c.514G>A, p.Asp172Asn) in the cytoplasmic seryl‐tRNA synthetase ( SARS ) gene. The mutation affects the enzymatic core domain of the protein and impairs its enzymatic activity, probably leading to reduced cytoplasmic tRNA Ser concentrations. The mutant protein was predicted to be unstable, which could be substantiated by investigating ectopic mutant SARS in transfected HEK293T cells. In the second family, we found a compound heterozygous genotype of the mitochondrial tryptophanyl‐tRNA synthetase ( WARS2 ) gene, comprising a nonsense mutation (c.325delA, p.Ser109Alafs*15), which very likely entails nonsense‐mediated mRNA decay and a missense mutation (c.37T>G, p.Trp13Gly). The latter affects the mitochondrial localization signal of WARS2, causing protein mislocalization. Including AIMP1, which we have recently implicated in the etiology of ID, three genes with a role in tRNA‐aminoacylation are now associated with this condition. We therefore suggest that the functional integrity of tRNAs in general is an important factor in the development and maintenance of human cognitive functions.